Fulfillment of Employee Welfare and Work Environment on Employee Performance in Jakarta - Rizal, Fahmi (Dinasti International Journal of Digital Business Management, 2023)
Employee welfare determines the success rate of the company to grow and development. focus is needed for the welfare of employees, especially from the aspects of salary, education, and health that can affect employee performance. This research examines the influence of salary, education, and work environment on employee performance in employees community in Jakarta . Primary data was obtained from the results of questionnaires distributed to respondents and then analyzed using a quantitative descriptive approach and multiple linear regression analysis techniques using the SPSS-25 tool. This research found several things. The first finding is that partially the level of well-being has a significant positive effect on the performance of employees. And the work environment has a great influence on improving employee performance.